Fecal microbiota transplantation for irritable bowel syndrome: a systematic review and meta-analysis of randomized controlled trials - Wang, Mancai; Xie, Xiaofeng; Zhao, Songbo; Ma, Xiaojuan; Wang, Zheyuan; Zhang, Youcheng (Frontiers in Immunology, 2023)
Objective Whether fecal microbiota transplantation (FMT) in patients with irritable bowel syndrome (IBS) is effective in improving outcomes remains controversial. We assessed the safety and efficacy of FMT for patients with IBS. Methods In this systematic review and meta-analysis, we searched PubMed, Embase, Web of Science, the Cochrane Library, the clinicaltrials.gov and International Clinical Trials Registry Platform (ICTRP) up to March 28, 2023. Randomized controlled trials (RCTs) compared the stool and capsule FMT with placebo in patients with IBS were included. Two authors independently assessed study eligibility, extracted the data, and assessed risk of bias. We did meta-analysis with RevMan, and the Stata software was used for sensitivity analysis and meta-regression. The GRADE system was used to assess the quality of evidences. Mean difference (MD) or standardized Mean difference (SMD) with 95% CI for continuous data, and risk ratios (RR) with 95% CI for dichotomous data were used with random-effects models. The primary outcomes included the clinical response rate and IBS-SSS score. This study is registered with PROSPERO. Results Nineteen reports from nine RCTs were included finally. Compared with the placebo, a single stool FMT could significantly decrease the IBS-SSS score at 1 month (MD=-65.75, 95%CI [-129.37, -2.13]), 3 months (MD=-102.11, 95% CI [-141.98, -62.24]), 6 months (MD=-84.38, 95%CI [-158.79, -9.97]), 24 months (MD=-110.41, 95%CI [-145.37, -75.46]), and 36 months (MD=-104.71, 95%CI [-137.78, -71.64]). It also could improve the clinical response rate at 3 months, 24 months, and 36 months, and increase the IBS-QoL score at 3 months, 24 months, and 36 months. FMT did not increase the serious adverse event. The risk of bias was low, and the quality of evidence based on GRADE system was moderate in the stool FMT group. However, we did not find positive effect of capsule FMT on patients with IBS based on the current available data. Conclusion A single stool FMT is effective and safe for patients with IBS. However, some factors may affect the effectiveness of FMT, and the relationship between the gut microbiome and the effect of FMT for IBS is still unclear.